Aging and ESL Learning among Older Adult Chinese-Speaking Immigrants (Global Journal of Human-Social Science, 2018)
How do older adult Chinese-speaking immigrants experience ESL learning in both classroom and informal community settings? This study analyzes the relation between aging and ESL learning. Based on the unique features of older adult population, the author demonstrates the strategies that administrators and ESL instructors can utilize to enhance the ESL learning experience for this population.
Keywords: ESL; chinese americans; chinese-speaking immigrants; identity; older adults